Obesity Enhances Disease Severity in Female Mice Following West Nile Virus Infection - Geerling, Elizabeth; Stone, E. Taylor; Steffen, Tara L.; Hassert, Mariah; Brien, James D.; Pinto, Amelia K. (Frontiers in Immunology, 2021)
A rise in adiposity in the United States has resulted in more than 70% of adults being overweight or obese, and global obesity rates have tripled since 1975. Following the 2009 H1N1 pandemic, obesity was characterized as a risk factor that could predict severe infection outcomes to viral infection. Amidst the SARS-CoV-2 pandemic, obesity has remained a significant risk factor for severe viral disease as obese patients have a higher likelihood for developing severe symptoms and requiring hospitalization. However, the mechanism by which obesity enhances viral disease is unknown. In this study, we utilized a diet-induced obesity mouse model of West Nile virus (WNV) infection, a flavivirus that cycles between birds and mosquitoes and incidentally infects both humans and mice. Likelihood for severe WNV disease is associated with risk factors such as diabetes that are comorbidities also linked to obesity. Utilizing this model, we showed that obesity-associated chronic inflammation increased viral disease severity as obese female mice displayed higher mortality rates and elevated viral titers in the central nervous system. In addition, our studies highlighted that obesity also dysregulates host acute adaptive immune responses, as obese female mice displayed significant dysfunction in neutralizing antibody function. These studies highlight that obesity-induced immunological dysfunction begins at early time points post infection and is sustained through memory phase, thus illuminating a potential for obesity to alter the differentiation landscape of adaptive immune cells.